2015
DOI: 10.1016/j.jana.2015.04.003
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Employment on Neurocognitive Reserve in Adults With HIV: A Review of the Literature

Abstract: The benefits of employment are enormous; being employed, one naturally: 1) socially engages with the public and colleagues/co-workers; 2) learns new skills to increase job productivity and competence; 3) establishes a routine that can prevent lethargy and boredom and may regulate sleep and healthy behaviors; 4) is provided purposeful and meaningful activity that may protect one from depression; and 5) gains income to pursue interests which are cognitively stimulating. All of these and other employment influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
1
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 70 publications
2
26
1
2
Order By: Relevance
“…Cognitive reserve may be supported by healthy behaviors such as physical exercise or good nutrition that simply promotes general health which benefits brain health. 8,9 On the contrary, cognitive reserve may be unsupported by unhealthy behaviors such as drug use, stress, and a sedentary lifestyle. 1013 Several studies have shown that in normal older adults, 14 as well as HIV-infected adults, 10 active engagement facilitates increased cognitive reserve and successful cognitive aging.…”
mentioning
confidence: 99%
“…Cognitive reserve may be supported by healthy behaviors such as physical exercise or good nutrition that simply promotes general health which benefits brain health. 8,9 On the contrary, cognitive reserve may be unsupported by unhealthy behaviors such as drug use, stress, and a sedentary lifestyle. 1013 Several studies have shown that in normal older adults, 14 as well as HIV-infected adults, 10 active engagement facilitates increased cognitive reserve and successful cognitive aging.…”
mentioning
confidence: 99%
“…There are several factors that can encourage positive neuroplasticity which is necessary to support cognitive reserve; these include physical activity, good mood support, stimulating and mentally challenging activities, and social interaction. In fact, even employment and volunteer work has been suggested recently as being an important vector for maintaining optimal cognitive functioning as people age (Vance, Cody, Yoo-Jeong, Jones, & Nicholson, 2015). Likewise, there are several factors that likewise promote negative neuroplasticity and reduce cognitive reserve, thus making people more vulnerable for age-related cognitive declines; these include depression and anxiety, loneliness, poor health, substance abuse, and lacking stimulating activities.…”
Section: Discussionmentioning
confidence: 99%
“…Based upon the literature, Vance et al described five mechanisms in which employment supports cognitive reserve: 1) learning new skills; 2) social engagement; 3) established routine/structure; 4) purpose/meaning; and 5) income (Figure 1). 12 …”
Section: Positive Neuroplastic Effects Of Employmentmentioning
confidence: 99%